(untitled) (Philological Studies, 2019)
The article is concerned with the emotional subject representations in syntactic structures. The emotional subject is represented in different structures. This means that the emotional sphere is very important for the Russian consciousness. Having analyzed the emotional subject representations it is possible to say that in general the emotional subject is more often represented by the oblique (dative, genitive, object, prepositional) cases than the nominative one. The syntactic structures are interpreted in the national world view aspect in order to understand differences between structures and their semantics better